Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10528-011-9475-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the CD36 Gene and Cardiovascular Risk Factors in Patients with Coronary Artery Disease Manifested at a Young Age

Abstract: This study investigates potential associations between CD36 gene variants and the presence of risk factors in Caucasians with coronary artery disease (CAD) manifested at a young age. The study group consisted of 90 patients; the men were ≤ 50 years old and the women were ≤ 55 years old. Amplicons of exons 4 and 5 including fragments of introns were analyzed by DHPLC. Two polymorphisms were found: IVS3-6 T/C (rs3173798) and IVS4-10 G/A (rs3211892). The C allele of the IVS3-6 T/C polymorphism was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In our previous study [16] the higher sCD36 plasma concentrations were significantly positively correlated with HDL-cholesterol and ApoA1 concentrations. We have recently identified [22] an association of CD36 gene rs3173798 polymorphism with younger age of MI and presence of type 2 diabetes. In the present study there were no differences in sCD36 plasma concentrations between patients with present and absent MI or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [16] the higher sCD36 plasma concentrations were significantly positively correlated with HDL-cholesterol and ApoA1 concentrations. We have recently identified [22] an association of CD36 gene rs3173798 polymorphism with younger age of MI and presence of type 2 diabetes. In the present study there were no differences in sCD36 plasma concentrations between patients with present and absent MI or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expression of microRNAs in critical polytraumatized patients is represented by the pro-inflammatory and pro-oxidative status (Kaya and Yildiz 2008;Rać et al 2012;Sagor et al 2015;Bonaventura et al 2016;Hayashi et al 2016). Hulsmans et al, studied the implications of microRNA in augmenting the inflammatory status.…”
Section: The Micrornas Expression In Sepsis and Its Implications In Nmentioning
confidence: 99%
“…For example, a study on CD36 (rs1761667) showed that obese women carrying the GG genotype exhibit lower thresholds of gustatory mechanisms for fat detection than those with the AA genotype (Mrizak et al, 2015). In addition, the A allele of IVS4-10 G/A and the C allele of IVS3-6 T/C have both been associated with myocardial infarction (Rać et al, 2012b). Rać et al (2012a) demonstrated that the GG genotype of CD36 was significantly correlated with higher concentrations of HbA1c compared with the AA genotype in obese children.…”
Section: Discussionmentioning
confidence: 99%